The effects of subacute exposure to a water-soluble cannabinol compound in male mice - Melissa M. Bailey; Mariah C. Emily Mills; Ashley E. Haas; Kelly Bailey; Robert C. Kaufmann (BMC, 2022)
Abstract Background Cannabinol (CBN) is one of the many cannabinoids present in Cannabis sativa and has been explored as a potential treatment for sleeplessness. The purpose of this study was to determine the physiological and behavioral effects of subacute exposure to therapeutic and low pharmacological levels of a mechanically formed, stabilized water-soluble cannabinol nano-emulsion (CBNight™). Methods Sixty-two male mice were randomly assigned to one of six treatment groups given CBNight™ at dosages designed to deliver 0mg (control) to 4 mg/kg of CBN daily via oral gavage for 14 days. In-cage behavior was observed at 30 minutes and at 2, 4, 8, and 16 hours after each dose. After 14 days, the mice were sacrificed and necropsied. Organs were weighed and inspected for gross abnormalities, and blood was collected via cardiac puncture for clinical chemistry. Results No dosage-dependent adverse effects on behavior, body mass, or blood chemistry were observed, except that the highest doses of CBNight™ were associated with significantly lower eosinophil counts. Conclusions The commercially available, water-soluble CBN compound employed in this study does not appear to cause adverse effects in mice; rather, it appears to be well tolerated at pharmacological levels. The findings of eosinopenia at higher doses of CBN and lack of hepatotoxicity at any dosage employed in this study have not been reported to date.